REGULATING BIOSAFETY OF GENETICALLY MODIFIED CROPS IN INDONESIA: LIMITS AND CHALLENGES (UUM Journal of Legal Studies, 2021)
The global use of genetically modified (GM) crops is rapidly expanding. While the advent of this agricultural biotechnology offers new promises to cater to the rising demand for Indonesia’s food security, the government should ensure its safety. This paper examines the regulatory regime over biosafety in Indonesia by considering the global fragmentation of biosafety regulation that debates its impact on environmental and health aspects. After Indonesia ratified the Convention on Biological Diversity and the Cartagena Protocol on Biosafety, which both specifically become the global guideline on how domestic biosafety policies are regulated, environmental and health issues are among the priorities which the use of GM crops contests to the precautionary approach. Amidst the insufficient scientific ground on its safety, GM crops' use is supposed to result in adverse impacts, and the suspicion over the safety of such a new cutting-edge agricultural technology ended with a series of rejections. This paper's results reveal that amongst the global contention over the regulatory regime on biosafety, which resulted in the bifurcation of the biosafety regulation, Indonesia has added to the new polarization. This polarization includes the release of GM crops certification, and Indonesia's desire to regulating biosafety deliberates over the definition and translation of biosafety in the domestic regulatory regime against the global regulatory diversity of biosafety.